Comparison of clinical features, disease activity, treatment and outcomes between late-onset and early-onset patients with systemic lupus erythematosus. A sex- and year at diagnosis-matched controlled study - Jarukit Mongkolchaiarunya; Antika Wongthanee; Nuntana Kasitanon; Worawit Louthrenoo (Advances in Rheumatology, 2023)
Abstract Background Several studies have compared the clinical features and outcomes of late- and early-onset systemic lupus erythematosus (SLE) patients. However, these previous studies were uncontrolled. The current study aimed to compare late- and early-onset SLE patients while controlling for sex and year at diagnosis (± 1 year). Methods The medical records of SLE patients in a lupus cohort from January 1994 to June 2020 were reviewed. Late-onset patients were identified as those with an age at diagnosis ≥ 50 years. The early-onset patients (age at diagnosis < 50 years) were matched by sex and year at diagnosis with the late-onset patients at a ratio of 2:1. Clinical manifestations, disease activity (mSLEDAI-2K), organ damage scores, treatment, and mortality were compared between the two groups. Results The study comprised 62 and 124 late- and early-onset patients, respectively, with a mean follow-up duration of 5 years. At disease onset, when comparing the early-onset patients with the late-onset patients, the latter group had a higher prevalence rate of serositis (37.0% vs. 14.5%, p < 0.001) and hemolytic anemia (50.0% vs. 33.9%, p = 0.034) but lower prevalence rate of malar rash (14.5% vs. 37.1%, p = 0.001), arthritis (41.9% vs. 62.1%, p = 0.009), leukopenia (32.3% vs. 50.0%, p = 0.022) and lymphopenia (50.0% vs. 66.1%, p = 0.034). The groups had similar SLE disease activity (7.41 vs. 7.50), but the late-onset group had higher organ damage scores (0.37 vs. 0.02, p < 0.001). The rates of treatment with corticosteroids, antimalarial drugs, or immunosuppressive drugs were not different. At their last visit, the late-onset patients still had the same pattern of clinically significant differences except for arthritis; additionally, the late-onset group had a lower rate of nephritis (53.2% vs. 74.2%, p = 0.008). They also had a lower level of disease activity (0.41 vs. 0.57, p = 0.006) and received fewer antimalarials (67.7% vs. 85.5%, p = 0.023) and immunosuppressive drugs (61.3% vs. 78.2%, p = 0.044), but they had higher organ damage scores (1.37 vs. 0.47, p < 0.001) and higher mortality rates/100-person year (3.2 vs. 1.1, p = 0.015). After adjusting for disease duration and baseline clinical variables, the late-onset patients only had lower rate of nephritis (p = 0.002), but still received fewer immunosuppressive drugs (p = 0.005) and had a higher mortality rate (p = 0.037). Conclusions In this sex- and year at diagnosis-matched controlled study, after adjusting for disease duration and baseline clinical variables, the late-onset SLE patients had less renal involvement and received less aggressive treatment, but had a higher mortality rate than the early-onset patients.